Ethical aspects related to dentistry remunerations - Palomer Roggerone, Leonor (Acta Bioethica, 2012)
There are different modalities to receive remunerations in liberal careers such as dentistry. In general, payment is done for actions carried out by time dedicated to execute them. In some cases, the amount of payment is directly related to the diagnosis of the patient. There is a conflict of interest in some of these modalities? To answer this question a bibliographical search was carried out on the topic, finding scarce literature on it. From the revised material, we can conclude that the problem is not the existence of a conflict of interest, but what brings an ethical dimension to the topic of remunerations is its resolution.